2020
DOI: 10.1136/bmjoq-2019-000833
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a pilot NHS-funded sore throat test and treat service in community pharmacies on provision and quality of patient care

Abstract: ObjectiveA National Health Service (NHS)-funded sore throat test and treat (STTT) service was introduced in selected pharmacies in two local health boards in Wales, as an extension to the national pharmacy common ailment scheme. The aim of this study was to evaluate the impact of STTT on provision and quality of patient care, namely antibiotic use, patient safety and general practitioner (GP) consultation rates.MethodsSecondary analyses of STTT consultation data to describe service outcomes, and routine data t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…A second study investigated data derived from a range of national databases providing pharmacy, GP, prescribing and secondary care data, to evaluate whether a pilot of an NHS funded pharmacy STTT service had an impact on antibiotic provision, patient safety and GP consultation rates. 11 No safety concerns were identified and findings suggested that STTT can be part of a collaborative approach aiming to re-balance uncomplicated sore throat management from general practice to community pharmacies whilst continuing to promote antibiotic stewardship. Data from all these 13 studies were triangulated and fed back to policy makers as part of an integrated approach to inform the service development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A second study investigated data derived from a range of national databases providing pharmacy, GP, prescribing and secondary care data, to evaluate whether a pilot of an NHS funded pharmacy STTT service had an impact on antibiotic provision, patient safety and GP consultation rates. 11 No safety concerns were identified and findings suggested that STTT can be part of a collaborative approach aiming to re-balance uncomplicated sore throat management from general practice to community pharmacies whilst continuing to promote antibiotic stewardship. Data from all these 13 studies were triangulated and fed back to policy makers as part of an integrated approach to inform the service development.…”
Section: Discussionmentioning
confidence: 99%
“…The service adopted a staged test and treat strategy, with pharmacists using clinical scoring tools (FeverPAIN and CENTOR) to complete an initial examination, offering a POCT to screen for the presence of Streptococcus A if threshold scores were met, and antibiotics, if needed, in the case of a positive POCT. The model of service delivery has been described elsewhere, 11 and is also summarized in Supplementary Table 1. A study looking at the impact of the service on provision of patient care in the community setting suggested that STTT may have a role in safely re-balancing uncomplicated sore throat management from general practice to community pharmacies whilst continuing to promote antibiotic stewardship.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose of the study, antibiotics could be supplied directly by the pharmacist under a Patient Group Direction. Follow-up was conducted on 51.9% of patients, of which 91.6% reported feeling better after using the service [ 55 ].…”
Section: Antimicrobial Stewardship In Community Pharmacymentioning
confidence: 99%
“…The study reported possible savings to the National Health Service (NHS) from the 41 general practitioner consultations avoided was among those patients at 2747 GBP in 2015 36 . An evaluation of a NHS sore throat test and treat service in Wales reported that the service was associated with a reduction in antibiotic prescriptions 37 . A United States study quantified the average amount of pharmacist time (25.3 min) required to complete a point‐of‐care test for a patient presenting with pharyngitis symptoms.…”
Section: Resultsmentioning
confidence: 99%